A Moral Measure of Capitalism? : Pioneers of Capitalism: The Netherlands, 1000-1800 - McCants, Anne EC (TSEG - The Low Countries Journal of Social and Economic History, 2024)
Like much recent historiography, especially that inspired by the so-called “new history of capitalism,” Prak and Van Zanden are interested in what they call the “how” and “why” of the emergence of a capitalist market economy in the premodern Low Countries Yet, unlike much of the literature in this vein which takes the early modern trans-Atlantic slave trade and the tobacco, coffee, tea, sugar and cotton plantation economies that it supported as capitalism’s founding moment, the authors begin their story solidly in the early Middle Ages.